Formulation of the bivalent prostate cancer vaccine with surgifoam elicits antigen-specific effector T cells in PSA-transgenic mice. Issue 43 (13th October 2017) - Karan, Dev
Abstract: We previously developed and characterized an adenoviral-based prostate cancer vaccine for simultaneous targeting of prostate-specific antigen (PSA) and prostate stem cell antigen (PSCA). We also demonstrated that immunization of mice with the bivalent vaccine (Ad5 -PSA+PSCA) inhibited the growth of established prostate tumors. However, there are multiple challenges hindering the success of immunological therapies in the clinic. One of the prime concerns has been to overcome the immunological tolerance and maintenance of long-term effector T cells. In this study, we further characterized the use of the bivalent vaccine (Ad5 -PSA+PSCA) in a transgenic mouse model expressing human PSA in the mouse prostate. We demonstrated the expression of PSA analyzed at the mRNA level (by RT-PCR) and protein level (by immunohistochemistry) in the prostate lobes harvested from the PSA-transgenic (PSA-Tg) mice. We established that the administration of the bivalent vaccine in surgifoam to the PSA-Tg mice induces strong PSA-specific effector CD8 + T cells as measured by IFN-γ secretion and in vitro cytotoxic T-cell assay. Furthermore, the use of surgifoam with Ad5 -PSA+PSCA vaccine allows multiple boosting vaccinations with a significant increase in antigen-specific CD8 + T cells. These observations suggest that the formulation of the bivalent prostate cancer vaccine (Ad5 -PSA+PSCA) with surgifoam bypasses the neutralizing antibody response, thus allowing multiple boosting. This formulation is also helpful for inducing an antigen-specific immune response in the presence of self-antigen, and maintains long-term effector CD8 + T cells.